(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
This paper presents and analyzes the results of a two-year study on the effect of the fertilization system on seed yield, dry plant biomass yield, and the proportion of seeds in the total biomass of sunflower plants. Formulation of the problem. Despite the large number of scientific publications devoted to various approaches to sunflower fertilization, the issue of evaluating the effectiveness of fertilization systems remains incompletely studied. This is explained by the introduction into production of new types of fertilizers, modern sunflower hybrids and varieties with different morpho-biotypes, and consequently, different responses to fertilizers. Climate change also plays a significant role in this regard, as it also influences, to a certain extent, the effectiveness of crop fertilization approaches. The purpose of the research. The objective of the study was to determine the combined effect of various combinations of pre-sowing, pre-planting, and root-zone application of mineral fertilizers on the seed yield and dry biomass of the sunflower hybrid SY Fenomeno under the conditions of the Left-Bank Forest-Steppe of Ukraine. Research methods. The study was conducted in 2024 and 2025 at the “Hryga” farm in the Poltava District of Poltava Oblast. The experiment was set up using the split-plot design. The first-order plots (factor A) consisted of four variants of root-zone fertilization of crops with the liquid fertilizer UAN32 at the V5–V6 stage: 1 – control (no fertilization); 2, 3, and 4 – UAN32 at doses of 65 l/ha (N20), 95 l/ha (N30), and 125 l/ha (N40), respectively. The second-order plots (factor B) consisted of five combinations of pre-sowing and top-dressing fertilizer applications: I – absolute control; II – pre-sowing application of ammonium sulfate at a rate of 100 kg/ha combined with top-dressing application of ammophos at a rate of 100 kg/ha (production control); III, IV, and V – pre-sowing application of sulfoammophos at a rate of 100 kg/ha combined with post-sowing application of the complex fertilizer MACROSTAR at rates of 100 kg/ha, 150 kg/ha, and 200 kg/ha, respectively. The area of the second-order plot was 210 m². Research methods. The highest average sunflower seed yield over two years was achieved in the treatment involving the root-zone application of UAN32 at a rate of 125 l/ha, combined with a top-dressing application of 200 kg/ha of Makrostar fertilizer, against a background of a pre-sowing application of 100 kg/ha of sulfoammophos – 2.72 t/ha. Compared to the control, the yield increase was 0.59 t/ha, or 28 %. At the same time, the yield was similar in the treatment involving topdressing with 150 kg/ha of Makrostar and root-zone application of UAN32 at a dose of 95 l/ha. The difference in seed yield between these variants in 2024 and 2025 was only 0.15 and 0.08 t/ha, respectively. Under the weather conditions of both years, the effectiveness of pre-sowing, co-sowing, and root-zone fertilizer application in terms of seed yield was virtually identical, indicating the advisability of these practices in years with varying weather conditions. In absolute terms, the increases in seed yield in 2024 and 2025 were virtually identical; in relative terms, they were higher under the less favorable weather conditions of 2024. In 2024, the highest dry biomass yield of sunflower plants – 9.39 t/ha, was achieved in the treatment involving the root-zone application of UAN32 at a rate of 125 l/ha (N40) against a background of pre-sowing application of sulfoammophos at a dose of 100 kg/ha and top-dressing with Makrostar fertilizer at a dose of 200 kg/ha (N18P40K24). At the same time, it was significantly higher than in all other variants. In 2025, a slightly different trend was observed, namely, the highest dry biomass yield of sunflower plants was also in this variant – 10.10 t/ha, however, it did not differ significantly from the variant with a Makrostar fertilizer application rate of 150 kg/ha in combination with 95 l/ha of UAN32. The difference between these variants was only 0.15 t/ha, or 1.5 %. An analysis of the proportion of seeds in the total biomass of sunflower plants revealed no significant fluctuations in this proportion under the influence of the factors studied. Only a tendency toward a decrease in the proportion of seeds in the total plant biomass was observed when the application rates of the Makrostar complex fertilizer were increased. This trend was more pronounced in 2025. Specifically, on average across the root-zone fertilization treatments, the seed proportion in the total biomass of sunflower plants in that year was 27.7 % in the treatment with the highest doses of pre-sowing and top-dressing fertilizers, whereas in the control for this factor, it was 28.5 %. Conclusions. The results of a two-year study demonstrated the high effectiveness of pre-sowing, co-sowing, and root-zone application of compound fertilizers in increasing seed yield and dry plant biomass. In terms of agronomic efficiency, the best options were the combination of pre-sowing application of sulfoammophos at a rate of 100 kg/ha (N20P20S14), co-sowing application of the Makrostar compound fertilizer at doses of 150 and 200 kg/ha (N14P30K18 and N18P40K24), and root-zone fertilization with the liquid fertilizer UAN32 at a dose of 95 l/ha (N30).